AKTIVITAS EKSTRAK BIJI TANAMAN MINDI MELIA AZEDARACH (L.) TERHADAP SPODOPTERA LITURA (F.) (LEPIDOPTERA: NOCTUIDAE) - Hamdani . (Universitas Lampung, 2005)
Activity of Melia azedarach (L.) seed extract against armyworm Spodoptera litura (F.) (Lepidoptera: Noctuidae). This study was conducted to evaluate the effectivenes and biological activity of Melia azedarach L. (Meliaceae) seed extract against armyworm, Spodoptera litura F. The first instar larvae were fed extract-treated cotton leaves for 2 days, then were maintained on untreated leaves until the third instar stage. Records were kept in regard to the larvae mortality and developmental time of surviving larvae from first instar to third instar. The result showed that Melia azedarach L. seed extract at consentration of 50 g of seeds/l of water (5%) exhibited moderate insecticidal activity against S. litura larvae (43.33 - 68.33% mortality). Addition of detergen at 0.2% to extract did not increase insecticidal activity of the extract. However, boiling seed extract at consentration of 50 g of seeds/l of water (5%) during 10 until 20 minutes increased insecticidal activity of extract (66.67 - 68.33% mortality). Generally, M. azedarach seed extract treatment did not affect developmental time of S. litura larvae.